1981
DOI: 10.1126/science.7268440
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine and Bradykinin Relax Intrapulmonary Arteries by Acting on Endothelial Cells: Role in Lung Vascular Diseases

Abstract: Acetylcholine and bradykinin produced potent relaxation of isolated canine intrapulmonary arteries contracted by serotonin, norepinephrine, or phenylephrine-provided the endothelium was left intact. Selective mechanical destruction of the endothelium transformed the activity of these substances from vasodilatation to vasoconstriction. Acetylcholine-induced relaxations, in the presence of intact endothelium, could be selectively inhibited competitively by atropine, but could not be inhibited by cyclooxygenase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
61
4

Year Published

1983
1983
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(71 citation statements)
references
References 5 publications
6
61
4
Order By: Relevance
“…Bradykinin is able to elicit an endotheliumdependent relaxation of a large variety of canine arteries (Chand & Altura, 1981;Cherry et al, 1982). Such a bradykinin-induced relaxation was also found to occur in pig aorta (Gordon & Martin, 1983), in bovine intrapulmonary artery and vein (Gruetter & Lemke, 1986a) and in bovine coronary artery (Angus et al, 1986b).…”
Section: Discussionmentioning
confidence: 97%
“…Bradykinin is able to elicit an endotheliumdependent relaxation of a large variety of canine arteries (Chand & Altura, 1981;Cherry et al, 1982). Such a bradykinin-induced relaxation was also found to occur in pig aorta (Gordon & Martin, 1983), in bovine intrapulmonary artery and vein (Gruetter & Lemke, 1986a) and in bovine coronary artery (Angus et al, 1986b).…”
Section: Discussionmentioning
confidence: 97%
“…Although the nature of EDRF has never been clearly explained, the activities of these EDRF inhibitors have led investigators to propose a number of possible sources for EDRF, including oxidative products of the lipoxygenase or epoxygenase pathways of arachidonate metabolism (25-27). Further studies showed that pulmonary artery strips had the capacity to respond to endothelium-dependent vasodilators (7,28). In view of these previous investigations, the results presented here demonstrate endothelium-dependent vasodilation in the pulmonary vascular bed, and are consistent with an important role of the endothelium in the modulation of the hypoxic pressor response of the intact pulmonary vascular bed through the release of EDRF.…”
Section: Discussionmentioning
confidence: 99%
“…As the role of the endothelium was investigated further, it was apparent that endothelium-dependent relaxation was due to release of a diffusible factor(s), as the relaxation was transferable in perfusate to vascular strips denuded of endothelium (6). This factor appeared to be a nonprostaglandin substance since vascular responsiveness to endothelium-dependent vasodilators was unchanged by treatment with cyclooxygenase inhibitors (7,8). However, the actions of these endothelium-dependent relaxing factors (EDRF)' were attenuated or blocked by multiple pharmacological agents, including the lipoxygenase antagonists eicosatetrayenoic acid (ETYA) and nordihydroguaiaretic acid (NDGA) (8) and the antioxidant hydroquinone (HQ) (6).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in microvessel beds of the cheek pouch and cremaster muscle of the hamster, arteriolar dilatation is produced by suffusing the tissues with hyperosmotic solutions. The dilatation requires between 2 and 5 min to reach full effect (Duling & Staples, 1976 Acetylcholine, bradykinin and histamine, however, evoke relaxation of large arteries in vitro by similar mechanisms which involve the release of a substance by the endothelial cell (Furchgott & Zawadzki, 1980;Chand & Altura, 1981a; Van de Voorde & Leusen, 1982). It was relevant, therefore, to test the response of large arteries from normal and diabetic animals to these agents.…”
Section: Discussionmentioning
confidence: 99%